Chanticleer and the fox - Chaucer, Geoffrey d. 1400.; Cooney, Barbara 1917-. (New York Crowell, 1958)
A sly fox tries to outwit a proud rooster through the use of flattery.
"Adaptation of the 'Nun's priest's tale' from the Canterbury tales."
Keywords: Fables; Animals -- Fiction